Application of Example Nonexample Learning Model Based on Brunerâs Theory in Identifying Plane Figure - Saragih, Sehatta; Suhermi, Zuhri D (Proceedings of the UR International Conference on Educational Sciences, 2018)
Lack of concept mastery is thought to be one of the causes of students difficulties in learning mathematics. Moreover, a learning management unsuitablewith the level of studentsâintellectual development and the low active role of students in learning is seen as a trigger for a tenuous control of concepts.This condition underlies the importance of a research, so the goal is to examine the impact of the application of ExampleNon Example learning models, guided by Bruners Theory. This study employs the design of pre-test and post-test Group Design with a sample of 199 people. Research data were collected by tests and analyzed descriptively and inferentially. The results show that the application of the Examples Non Examples model based on Brunerâs theory contributes significantly to improve students understanding ofthe concept of plane figure by 47.8%.